Clinical Features of Severe Malnutrition at the Pediatric Ward of Tembakau Deli Hospital, Medan - Gabriel Panggabean; Faisal Faisal; Ramyuzal Nasution; M. Sjabaroeddin Loebis; Zakaria Siregar (Paediatrica Indonesiana, 1990)
Six hundred and fifty seven hospitalized patients under five in Child Health Department Hospital Tembakau Deli Medon, from January 1988 until December 1988 had been investigated retrospectively. Severe PCM are found 12 (1.8%), consisting of 7 (58.3%) boys and 5 (41. 7%) girls. Most cases were found at the age of 1 - 2 years (33.3%). Marasmus were found in 5 cases (41. 7%), Marasmic kwashiorkor in 4(54%), while Kwashiorkor in 3 cases (25%). Clinical features of the patients are as follow: hepatomegaly 7 (58.3%), anorexia 6 (50%), old man face 5 (41.7%), subcutaneous fat decrease 5 (41. 7%), thinsparse easily pick hairs 5 (41. 7%), muscle hypotrophy 5 (41. 7%), edema of the lower extremity 4 (33 .3%), crazy pavement dermatosis 2 (16. 7%). All patients were hospitalized combined with other diseases as chronic diarrhea 6 (50%), bronchopneumonia 5 (41.7%) and ascariasis 4 (33.3%). Mortality in 1 patient.